Comparison of decaffeinated green tea and green coffee with metformin and empagliflozin on the GALNT2 and GALNT3 mRNA expression in metabolic syndrome rats - Bahar, Mokhamad Aswin; Rohman, Mohammad Saifur; Kurnianingsih, Novi (Universitas Brawijaya, 2026)
Background: Aberrant protein glycosylation mediated by the UDP-N-acetylgalactosamine:polypeptide N-acetylgalactosaminyltransferase (GALNT) family has been implicated in the pathogenesis of metabolic syndrome (MetS), yet the roles of GALNT2 and GALNT3 remain poorly characterized. Objective: This study aimed to evaluate the modulatory effects of decaffeinated green tea and green coffee on GALNT2 and GALNT3 mRNA expression in MetS rats, compared with standard therapies, metformin and empagliflozin. Methods: Twenty-five male Sprague Dawley (SD) rats were divided into five groups randomly: (1) MetS rats (METS), (2) MetS rats treated with 300 mg/kgBW decaffeinated green tea and 200 mg/kgBW decaffeinated green coffee (TKD), (3) MetS rats treated with 500 mg/kgBW metformin (MFN), (4) MetS rats treated with 30 mg/kgBW empagliflozin (EMPA), and (5) negative control (NC). The MetS model was induced using a high-fat, high-sucrose (HFHS) diet followed by streptozotocin injection (30 mg/kgBW). After 10 weeks, the treatment groups received interventions for 9 weeks. GALNT2 and GALNT3 mRNA expression was investigated using reverse transcription polymerase chain reaction (RT-PCR).. Result: TKD and MFN tended to decrease GALNT2 and increase GALNT3 mRNA expression, although the differences were not significant statistically compared to the METS group (p>0.05). EMPA decreased GALNT2 and increased GALNT3 mRNA expression significantly compared to the METS group (p<0.05). Conclusion: The significant effect of EMPA on GALNT2 and GALNT3 mRNA expression suggests its therapeutic potential in targeting glycosylation pathways in MetS. Although TKD and MFN exhibited similar trends with EMPA, the lack of statistical significance suggests the need for further study.